Conversational Implicature in Dialogue of “Layar Terkembang” Novel by Sutan Takdir Alisjahbana - Tika Mulyani; Meisuri Meisuri; Widya Andayani (Universitas Negeri Medan, 2021)
This research dealt with ConversationalImplicature in Dialogue of Layar TerkembangNovel by Sutan Takdir Alisjahbana based on Grice’sTheory and it was aimed to finding out the types ofconversational implicature, and to describe whythe certain type of conversational implicaturebecomes dominant. This research was conductedby using descriptive qualitative method. Thesource of the data was taken from LayarTerkembang novel by Sutan Takdir Alisjahbana,Then the dialogue of the novel as the data for theresearch. The findings showed that there were twotypes of conversational implicature in theprocedures namely Generalized ConversationalImplicature belong to 33 utterances andParticularized Conversational Implicature belongto 36 utterances. So, the most dominant types ofconversational implicature between the maincharacters in the novel was particularizedconversational implicature because it morecontained ambiguity, implicit meaning, conveyedan additional meaning, and their response did notrelevant with every question and also it cannoteasily to understand what he/she was talkingabout